Cough cough: discovering tuberculosis (Research, Society and Development, 2020)
Topics of great importance, such as tuberculosis, are plausible to be addressed within the school community since it is a disease with great occurrence and relevance. The aim of the project was to promote the knowledge of the school community about the importance of tuberculosis, ensuring the dissemination of information to the target audience. The project was carried out at Escola Caminho das Estrelas, located within the Launch Center of the Municipality of Alcântara - Maranhão. The teaching unit includes elementary education for 132 children from the 1st to the 9th grade. All students were pre-evaluated to measure their knowledge about tuberculosis. Then, the theme was explored through a play with the presence of the project's executing members, where concepts, symptoms, diagnosis and treatment of the disease were contemplated. Subsequently, the students were again evaluated, in order to measure the students' learning and performance against the proposed action. It was possible to conclude through the intervention, the students (1st to 9th grade) have little knowledge about microbiology, in addition, 36 (60%) of the children in group 1 had never heard about tuberculosis and 48 (80%) did not know about the BCG vaccine scar. Group 2, 4.33% believe that the treatment of tuberculosis is carried out through teas or surgery. Therefore, interventions are necessary so that children and adolescents know as much information about tuberculosis, ensuring the dissemination of information by them to the community in general around them.